2015
DOI: 10.1186/s12939-015-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Usual source of care and the quality of primary care: a survey of patients in Guangdong province, China

Abstract: IntroductionUsual source of care (USC) refers to the provider or place a patient consults when sick or in need of medical advice. No studies have been conducted in China to compare the quality of primary care provided with or without USC. The purpose of this study was to fill this gap in the literature by examining the quality of primary care provided between those having a USC and those without. Results of the study would provide implications for policymakers in terms of improving primary care performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
2
24
0
3
Order By: Relevance
“…It suggested that doctors would not seek advice from patients or their family members when making treatment plans. This finding was in line with several previous studies [33][34][35]. Though many experts called for more autonomy and participation for patients, it was difficult for patients to achieve equality in their medical decisions due to insufficient medical knowledge or communication barriers [13,36].…”
Section: Discussionsupporting
confidence: 91%
“…It suggested that doctors would not seek advice from patients or their family members when making treatment plans. This finding was in line with several previous studies [33][34][35]. Though many experts called for more autonomy and participation for patients, it was difficult for patients to achieve equality in their medical decisions due to insufficient medical knowledge or communication barriers [13,36].…”
Section: Discussionsupporting
confidence: 91%
“…Limitations of the study include: 1- the definition of the outcome variable – USC – refers to a provider or place a patient consult when sick or in need of medical advice and is considered one of the hallmarks of primary health care [5]. Furthermore, USC is used in many self-reported surveys and is operationalized through questions such as “Is there one particular place that you go if you are sick or need advice about your health?” and “Is there a regular doctor you usually see at this place?” [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…” A growing body of research indicates that having a USC improves timely access to medical care, improves quality of care received, and results in improved health status (23456). Primary care can be identified as the specific set of health care functions served by a USC.…”
Section: Introductionmentioning
confidence: 99%